Contemporary Synthetic Strategies towards Secosteroids, abeo-Steroids, and Related Triterpenes - Noack, Florian; Heinze, Robert C.; Heretsch, Philipp (Synthesis, 2019)
Steroids have long been sought after as synthetic targets. Their rearranged counterparts, though, have only recently received more attention, when isolation and biological testing programs revealed several molecular entities that were both structurally intriguing as well as biologically relevant. This review will highlight contemporary synthetic approaches towards the growing class of seco- and abeo-steroids and some related triterpenoid natural products.1 Introduction2 Cyclocitrinol2.1 Li’s Synthesis of Cyclocitrinol2.2 Gui’s Synthesis of Cyclocitrinol3 Strophasterol3.1 Heretsch’s Synthesis of Strophasterol A3.2 Kuwahara’s Synthesis of Strophasterols A and B4 Pleurocin A/Matsutakone and Pleurocin B4.1 Heretsch’s Synthesis of Pleurocin A/Matsutakone and Pleurocin B5 Aplysiasecosterol A5.1 Li’s Synthesis of Aplysiasecosterol A6 Glaucogenins C and D6.1 Tian’s Syntheses of 5,6-Dihydro-glaucogenin C and Glaucogenin D7 Physalin B7.1 Sodeoka’s Synthesis of the DFGH Ring System of Physalin B8 Limonin8.1 Hirama’s Synthesis of (±)-Limonin9 Schiglautone A9.1 Ding’s Synthesis of (±)-atrop-Schiglautone A10 Conclusion
Keywords: abeo-steroids; biomimetic synthesis; secosteroids; semisynthesis; total synthesis; triterpenes